2022
DOI: 10.1002/rcs.2437
|View full text |Cite
|
Sign up to set email alerts
|

Robotic single port anti‐reflux surgery: Initial worldwide experience of two cases with a novel surgical approach to treat gastroesophageal reflux disease

Abstract: Introduction To date, no anti‐reflux operations have been reported with the new da Vinci Single‐Port (single port (SP)) robotic platform. We aimed to describe this novel surgical approach and evaluate its safety and feasibility. Methods All robotic SP operations were performed under an Institutional Review Board approved protocol. Results Two patients underwent robotic SP anti‐reflux surgery through a single incision of 2.7 cm (one Nissen‐fundoplication and one re‐Redo Nissen‐fundoplication). The mean docking‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The current version of the robotic surgical system allows single port surgery with articulating cameras and hand tools, enabling its application in major oncological surgical procedures, causing less postoperative pain, better cosmetic results, and lower hernia rates [ 92 ]. Single port liver surgery should limit the abdominal wall trauma even more, especially in case of lesions in the posterosuperior segments, which are somewhat more difficult to reach with open and laparoscopic methods and require larger incisions.…”
Section: Future Outlookmentioning
confidence: 99%
“…The current version of the robotic surgical system allows single port surgery with articulating cameras and hand tools, enabling its application in major oncological surgical procedures, causing less postoperative pain, better cosmetic results, and lower hernia rates [ 92 ]. Single port liver surgery should limit the abdominal wall trauma even more, especially in case of lesions in the posterosuperior segments, which are somewhat more difficult to reach with open and laparoscopic methods and require larger incisions.…”
Section: Future Outlookmentioning
confidence: 99%
“…Among the included studies, 36 were case reports [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ], 52 were noncomparative studies [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ,…”
Section: Resultsmentioning
confidence: 99%
“…Forty-five (43.7%) authors reported the surgical background of the operating surgeon and his previous experience [ 26 , 31 , 33 , 45 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 62 , 64 , 67 , 69 , 76 , 77 , 79 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 94 , 96 , 99 , 102 , 103 , 104 , 105 , 106 , 108 , 109 , 110 ]. A structured training process of the surgical team on the adopted system was reported by 28 (27.2%) authors [ 26 , 40 , 47 , 48 , 49 , 51 , 52 ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations